Teknik Pemotongan Kuku Sapi Pejantan Limousin - A Gustono; I Panjaitan; C A Patria (PETERPAN (Jurnal Peternakan Terapan), 2020)
Limousin is one of the beef cattle breeds of the Taurus boss which was successfully devised and developed in France. In the maintenance of one of the management that is considered is care / nail cutting. Cutting is done to maintain performance while climbing teasher cow when semen collection process, avoid or prevent the nail grows abnormally, the limping leg, footrot (nail rot) and laminitis. The purpose of this paper is to describe the technique of cutting nails in Limousin bulls. Implementation methods of data collection by observation, interviews and secondary data collection. The process of cutting the nails using a cutting knife (kamagata teito), rennet, grinding, measuring bar, chisel, small hammer, hirauci rope (rope that has been done by packing). Mechanical cut your nails done by a process handling bulls of the cage toward the maintenance of cut nails, bulls put the nail cutting table (table hooves trimming), feet and body bound to the mast nail cutting table and cutting nails.Â